2016
DOI: 10.1021/acs.energyfuels.6b00583
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle and Non-legislated Gaseous Emissions from a Gasoline Direct-Injection Car with Ethanol Blend Fuels and Detergent Additives

Abstract: Ethanol as an engine fuel emits less pollutants than gasoline, is a completely renewable product with good ecological implications, and has the potential to reduce greenhouse gas emissions. However, ethanol–gasoline blends present a multitude of technical challenges to engine operation, including the creation of adverse engine deposits, especially on inlet valves and injector tips. Special detergent–dispersant additives in ethanol–gasoline blends are the most effective way of bypassing these technical challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…According to literature, there are usually no measurable concentrations of NO 2 , N 2 O, and HCHO with a correctly working three-way catalyst (below 1 ppm). 30 In summary, blending with ethanol induced a moderate decrease in CO 2 (10−15%) and overproportional reductions of CO (76−87%) and PN (77−97%) emissions. Transient versus steady driving has a large impact on PN and CO emissions, indicating that the vehicle, when operated with gasoline (E0), often is in fuel-rich and oxygen-deficient conditions.…”
Section: ■ Experimental Sectionmentioning
confidence: 89%
“…According to literature, there are usually no measurable concentrations of NO 2 , N 2 O, and HCHO with a correctly working three-way catalyst (below 1 ppm). 30 In summary, blending with ethanol induced a moderate decrease in CO 2 (10−15%) and overproportional reductions of CO (76−87%) and PN (77−97%) emissions. Transient versus steady driving has a large impact on PN and CO emissions, indicating that the vehicle, when operated with gasoline (E0), often is in fuel-rich and oxygen-deficient conditions.…”
Section: ■ Experimental Sectionmentioning
confidence: 89%
“…Costagliola et al [22] studied the influence of four bioethanol-gasoline blends prepared with 10%, 20%, 30%, and 85% ethanol by volume in gasoline, and CO 2 was reduced by 7% when fueled with E85 compared to the gasoline fuel. Stępień et al [23] investigated a flex-fuel direct-injection vehicle with ethanol-gasoline blend fuels containing 10% or 85% ethanol with special consideration of nanoparticle and non-legislated gaseous emissions. It indicated that nanoparticle emissions from ethanol-gasoline blends of E85 showed the lowest PN (particle number) concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The cold start engine condition is an important factor influencing PN emissions from GDI engines. At cold-start, the heat transfer the combustion chamber surface to the fuel-air mixture is considerably reduced and thus less fuel vaporisation and air-fuel mixing will occur, resulting in a heterogeneous charge and localized fuel-rich regions [97,98]. The cold-start particulate emission accounted for more than 50% of the total PN emission from gasoline direct-injection vehicles over a drive cycle [99].…”
Section: Cold Start and Ambient Temperature Conditionsmentioning
confidence: 99%